Acute Sensory Neuronopathy following Enterovirus Infection in a 3-Year-Old Girl - Chiu, Chih-Chin; Yang, Chen-Ya; Yang, Tsui-Fen; Lin, Kon-Ping; Huang, Shou-Hsien; Wang, Jia-Chi (Neuropediatrics, 2017)
Acute sensory neuronopathy (SNN) is a rapidly developing peripheral nervous system disease that primarily affects sensory neurons in the dorsal root ganglion or trigeminal ganglion, leading to the impairment of sensory axons. SNN is notably uncommon in childhood; only three cases of childhood or adolescent SNN have been reported to date. Moreover, SSN has never been reported in association with enterovirus infection. Here, we report the case of a 3-year-old girl who was initially diagnosed with enterovirus infection based on the presentation of fevers, rashes on all extremities, and ulceration over the posterior pharynx. Nine days later, she presented with ataxic and wide-based gait and dysmetria affecting the extremities, with an absence of sensory nerve action potentials in the upper and lower limbs. The patient was diagnosed with acute SNN based on the criteria developed by Camdessanché et al in 2009. To our knowledge, this is the youngest case of SNN reported to date. In addition, this case reveals that enterovirus infection can be associated with acute SNN in children in rare cases. Accurate diagnosis relies on clinical suspicion, comprehensive knowledge of the patient's history, and careful characterization of abnormal findings in electrodiagnostic studies.
Keywords: acute sensory neuronopathy; ataxia; enterovirus; ganglionopathies; herpangina